Capacidade para o trabalho na enfermagem: relação com aspectos psicossociais do trabalho e distúrbios psíquicos menores - Prochnow, Andrea (2012)
This study aimed to analyze the association between high strain at work, minor psychological disorders and reduction of work ability of nursing workers. The central hypothesis is that the associations are positive. This is a cross-sectional epidemiological study performed with 498 nursing workers at a public university hospital in the State of Rio Grande do Sul, Brazil. We used the Brazilian versions of the Work Ability Index, Job Stress Scale and Self-Report Questionnaire-20 from a database collected in 2009. Data analysis was performed through PASW 18.0 by means of descriptive and multivariate statistics. Among the participants, 29,7% were classified under high strain at work, 33,7% with suspicion of minor psychological disorders and 43,3% with reduced work ability. The chances that workers under high strain present work ability reduced were higher (OR=2.09; IC95%1.25-3.51) when compared to those classified under low strain, even after adjustments of possible confounders (gender, age and function). Similarly, workers under suspicion of minor psychological disorders had more chances (OR= 2.70; IC95%=1.59-4.57) to be classified with reduced work ability when compared to those under no suspicion, even after adjusting for possible confounding factors (gender, schooling, working hours, other job, state of health, current state of health, sleep, smoking, age). It is concluded that the results confirm the hypothesis investigated. It is necessary to implement collective measures (managers and employees), health promotion and prevention of diseases, which may contribute to the maintenance of the work ability of this population.